Intuitive eating is associated with glycaemic control in adolescents with type I diabetes mellitus. (1st January 2016) - Wheeler, B.J.; Lawrence, J.; Chae, M.; Paterson, H.; Gray, A.R.; Healey, D.; Reith, D.M.; Taylor, B.J.
Abstract: Background: While there have been considerable advances in the medical management of type 1 diabetes mellitus (T1DM), for many, glycaemic control remains substandard. Nutrition and eating behaviour are important additional factors to consider with regards to T1DM management and outcomes. Intuitive eating is one such factor, and has not previously been investigated in T1DM. With this in mind, we undertook a study examining the relationship between intuitive eating and glycaemic control in adolescents with T1DM. Methods: A case-control study of adolescents with established T1DM, and age/sex matched controls was conducted. Demographic information, the Intuitive Eating Scale (IES), and HbA1 c were collected. Statistical analysis was undertaken to explore associations between the IES and HbA1c as a marker of glycaemic control. Results: Data on 38 adolescents with T1DM, and 39 age/sex matched controls were obtained. Those with T1DM had significantly lower (by 0.5 SD) IES scores compared to controls (p = 0.009). Higher values of both total IES and the Eating for physical rather than emotional reasons subscale were associated with lower HbA1c: HbA1c 22% lower/whole unit increase in total IES mean score, HbA1c 11% lower/whole unit increase in Eating for physical rather than emotional reasons mean score, p = 0.017 and p = 0.009 respectively. Conclusion: In adolescents with T1DM, there appears to be a strong association between intuitive eating, in particular the effect of emotion on eating, and glycaemic control. In addition, those with T1DM have lower scores for their intuitive eating behaviour compared to controls. Emotional eating could be a future target for screening and potentially intervening in those with T1DM, as part of a wider treatment package to improve glycaemic control. Continuing efforts are needed to fully understand the important dynamics of diabetes, adolescence, diet, emotion, and how these factors affect long term outcomes in those with T1DM. Highlights: This is the first study to examine intuitive eating (IE) in patients with type I diabetes mellitus (T1DM). In adolescents with T1DM, lower levels of IE, were strongly associated with worse glycaemic control. Of the three subscales of IE, the effect of emotion on eating was most strongly associated with worse glycaemic control. In addition, adolescents with T1DM have subtle reductions in their intuitive eating behaviour compared to controls.